ANXIETY LEVEL IN DANCERS BEFORE AND AFTER THE COMPETITION (Fiep Bulletin - online, 2016)
The study analyses the level of anxiety in dancers before and after the competition. There was a participation of 49 dancers of both sexes in Classical Ballet mode and enrolled in the senior category, group subgenre, of the 31stJoinville Dance Festival in the city of Joinville - SC, in 2013, with ages between 16 and 30 years. For data collection, it was possible to use a questionnaire containing general information on physical activity, dance and anxiety through the State-Trait Anxiety Inventory (IDATE). Dancers answered the survey at the presentation place, about 30 minutes before and after the competition. It was necessary to utilize inferential and descriptive statistics through Stata software, version 11.0. The results indicated that before the presentation 77.5% of dancers had a mean level of anxiety, and 14.3% showed high levels of stress. After the presentations, it was possible to observe some differences. High anxiety dropped from 14.3% to 4.1%, medium and low anxieties had a non-significant increase in dancers. It is noteworthy that no significant relationship was found between anxiety level, gender, age and experience time with dancing. It can be concluded that dancers had a mean level of anxiety during the dance festival competition. The principal stress decreases were observed among women, dancers, teenagers, those people with injuries and with an average experience in the dance. The groups aim to achieve the highest level of the festival; therefore, these dancers suffer psychological pressures that lead to stress and anxiety.
Keywords: Anxiety; Dance; Dancers.